Kesultanan Buton Dalam bingkai Ketatanegaraan dan Budaya Indonesia - Rahmadhona, Rahmadhona (UI Scholars Hub, 2023)
Buton is a region located in Bau-Bau City, Southeast Sulawesi. The Sultanate of Buton began to show its existence since the beginning of the 15th century after previously running a government system with royal government. The Buton Sultanate, based on Islam, ran a democratic system of government. The state administration of the Buton Sultanate is interesting to discuss because its power structure is controlled by two groups, but all of its people have the same position in voice and politics. This paper is compiled using the literature study method and presents the results descriptively.